2007
DOI: 10.1172/jci28764
|View full text |Cite
|
Sign up to set email alerts
|

Gain-of-function mutant of angiotensin II receptor, type 1A, causes hypertension and cardiovascular fibrosis in mice

Abstract: The role of the renin-angiotensin system has been investigated by overexpression or inactivation of its different genes in animals. However, there is no data concerning the effect of the constitutive activation of any component of the system. A knockin mouse model has been constructed with a gain-of-function mutant of the Ang II receptor, type 1A (AT 1A ), associating a constitutively activating mutation (N111S) with a C-terminal deletion, which impairs receptor internalization and desensitization. In vivo con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
53
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 52 publications
(57 reference statements)
8
53
0
1
Order By: Relevance
“…In several GPCRs, gain-of-function mutations are causative of diseases, but any activating mutations in the coding region of the AT 1 receptor gene have not been identified in hypertension or primary hyperaldosteronism. 9,10 Although knock-in mice with a constitutively activating mutation (substitution of Asn 111 to Ser with a C-terminal deletion) showed low-renin hypertension and progressive fibrosis in kidney and heart, 11 it remains unclear whether constitutive activity of the native AT 1 receptor leads to some phenotypic abnormalities even under circumstances where the production of Ang II is genetically inhibited.…”
mentioning
confidence: 99%
“…In several GPCRs, gain-of-function mutations are causative of diseases, but any activating mutations in the coding region of the AT 1 receptor gene have not been identified in hypertension or primary hyperaldosteronism. 9,10 Although knock-in mice with a constitutively activating mutation (substitution of Asn 111 to Ser with a C-terminal deletion) showed low-renin hypertension and progressive fibrosis in kidney and heart, 11 it remains unclear whether constitutive activity of the native AT 1 receptor leads to some phenotypic abnormalities even under circumstances where the production of Ang II is genetically inhibited.…”
mentioning
confidence: 99%
“…13 Moreover, AT 1 R G-protein coupling is sufficient to trigger cardiomyocyte hypertrophy, as seen with [N111G]AT 1A R. This observation is consistent with a recent knock-in study using N111S/⌬329 AT 1 R, which found that mice had significantly larger heart weight/body weight ratios and elevated brain natriuretic peptide levels, although the more profound phenotype was that of hypertension and cardiac fibrosis. 34 Although G␣ q/11 is the obvious candidate for mediating the G protein-dependent effects described herein, it is important to note that other G-protein subunits can be activated by the AT 1 R in both cardiomyocytes and vascular smooth muscle cells. 35 Functional selectivity also describes the ability of ␤-arrestins to act as ligand-regulated scaffolds.…”
Section: Discussionmentioning
confidence: 92%
“…Mice expressing a constitutively active AT1A receptor develop renal and cardiac fibrosis and diastolic dysfunction and present with a moderate and stable increase in blood pressure. This hypertension is associated with a low plasma renin concentration and a normal aldosterone concentration, leading to an increase in plasma ARR (65). These results suggest that, in humans, modifications or defects in the RAS may contribute to the high-aldosterone, low-renin form of hypertension and, in extreme cases, to mineralocorticoid excess.…”
Section: Mineralocorticoid Excess: Insights From Animal Modelsmentioning
confidence: 90%
“…The role of the RAS has been investigated in numerous experimental mouse models (63,64,65). Mice lacking the AngII receptor type 1A (AT1A receptor) have low blood pressure (63), whereas female mice overexpressing AT1A receptor display high blood pressure (64).…”
Section: Mineralocorticoid Excess: Insights From Animal Modelsmentioning
confidence: 99%